KREATIVITAS, INOVASI, DAN DAYA SAING BISNIS SEBAGAI DETERMINAN KEBERHASILAN USAHA: STUDI VERIFIKATIF PADA WIRAUSAHAWAN MUDA DI KOTA TASIKMALAYA - Yayan Mulyana; Alfin Nur Arifah (Journal of Business And Entrepreneurship, 2026)
This study examines the influence of creativity, innovation, and business competitiveness on the business success of young entrepreneurs in Tasikmalaya City. The study is positioned as a verification study that follows up on gaps left by prior literature examining the same three variables in the same context. A quantitative survey design was employed. The population comprised active young entrepreneurs running independent businesses in Tasikmalaya City, with an unknown population size. A sample of respondents was selected through purposive sampling. Data was analyzed using multiple linear regression. The results show that creativity has no significant partial effect on business success, while innovation and business competitiveness each have a significant positive effect. Simultaneously, the three variables significantly affect business success, with a substantial portion of the variance in business success explained by the model. These findings confirm innovation as the most dominant determinant, while opening room for future research to test innovation as a mediator between creativity and business success.